Painful shoulder in hemiplegia: Prevention and treatment - S. Irwin-Carruthers; M. J. Runnalls (AOSIS, 1980)
The painful shoulder which occurs in hemiplegia, is discussed. Possible mechanisms causing the pain, preventative measures based on the neurodevelopmental approach to treatment and therapeutic measures including treatment by means of passive movement, are described.